(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2022)
The purpose of this study was to determine the effect of spacing on the growth of seaweed Halymenia sp with the off-bottom method, and determine the spacing that gave the best effect on the growth of seaweed Halymenia sp with the off-bottom method. This research was conducted in Kastela coastal waters, Ternate Island District, Ternate City. The initial weight of the Halymenia sp clump used refers to the initial weight of the K. alvarezii clump which is about 50 g/clump. The stretch rope used is a polyethylene (PE) rope with a diameter of 4 mm and a length of 15 m with a distance of 1 m between the stretch ropes. Maintenance is carried out by the off-base monoline method. Data analysis was used to determine the growth of cultivated Halymenia sp seaweed. The data analyzed were absolute weight growth data, which was obtained from the difference between the average weight at the end of rearing and the initial weight when stocked/planted and the relative growth rate. The results showed that the spacing of seaweed Halymenia sp had a very different effect on absolute weight growth and relative growth of seaweed Halymenia sp, where a 25 cm spacing gave the best results on absolute weight growth and relative growth of seaweed Halymenia sp.